The Application of The Teams Assisted Individualization (TAI) Learning Model to Improve Learning Outcome of The Starter Motor Electrical System in VHS - Mike Elly Anitasari; Rakha Rakha; Yusri Bin Kamin; Muhammad Nurtanto; Suyitno Suyitno (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
This research was carried out at Vocational High School (VHS), where the student’s abilities for The Starter Motor Electrical System were still low. The objectives of the study were: to know (1) the application of the TAI (Team Assisted Individualization) learning model for the Motor Starter Electrical System learning in VHS; (2) the improvement in learning outcomes and the percentage of student graduation in the Motor Stater Electrical System learning with the TAI application learning model in VHS; (3) the extent to which the escalation of learning outcomes and the percentage of student graduation in the Motor Stater Electrical System learning after the TAI learning model application. This research belongs to Classroom Action Research, and the subjects were the VHS students. Data were collected using observation methods and test instruments. After the data were obtained, it was analyzed using descriptive analysis techniques. The research results show that: (1) The application of learning using the TAI learning model is carried out in the planning, action and closing stages. (2) The implementation of the TAI learning model can improve students’ learning outcomes, (3) the percentage of students’ graduation of 33.33% with an average score of 60.55 was getting higher to 58.33% in the first cycle with an average value of 69.02 and 94.44% in the second cycle with an average value of 78.47, respectively. It indicates the escalation of the average value of the students’ learning outcomes by 9.45 and the percentage of students’ graduation by 36.11%, respectively.